Influence of Part-Time Job on Academic Performance of Selected Grade 12 Humanities and Social Sciences Students of Bestlink College of the Philippines: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Most challenges that students confront can have an impact on academic success. This maytake into account things like working while going to school. Many students make a point ofworking while in class. However, other students who are employed don't truly struggle withmoney. Work part-time jobs that are linked to intended careers to develop abilities. Themajority of students work due to difficulties with finances.The utilization of online learning demonstrates that it is quite beneficial during a pandemic toadapt to the new normal. Even though some students find it to be quite beneficial, somestudents are still struggling to adjust to the new learning environment. Many students arehaving difficulties as a result of the epidemic. Mostly those who work and studysimultaneously. Others might lose jobs, which could have an impact on education. Due to alack of funding, many families are unable to access education.Due to a lack of funding, many families are unable to access education. Requiring a student tocontinue working while a student to support the education Students' GPAs higher thanexpected even if working a part-time job. However, compared to individuals who don't havepart-time employment, many working students took longer to complete degrees.
Keywords: Education